You can't pay me to quit: the failure of financial incentives for smoking cessation in head and neck cancer patients. Issue 3 (15th February 2016) - Ghosh, A; Philiponis, G; Bewley, A; Ransom, E R; Mirza, N
Abstract: Objective: A prospective randomised study was conducted at a tertiary care hospital to evaluate the effects of financial incentives for smoking cessation targeted at a high-risk population. Methods: Patients with a past history of head and neck cancer were voluntarily enrolled over a two-year period. They were randomised to a cash incentives or no incentive group. Subjects were offered enrolment in smoking cessation courses. Smoking by-product levels were assessed at 30 days, 3 months and 6 months. Subjects in the incentive group received $150 if smoking cessation was confirmed. Results: Over 2 years, 114 patients with an established diagnosis of head and neck cancer were offered enrolment. Twenty-four enrolled and 14 attended the smoking cessation classes. Only two successfully quit smoking at six months. Both these patients were in the financially incentivised group and received $150 at each test visit. Conclusion: Providing a financial incentive for smoking cessation to a population already carrying a diagnosis of head and neck cancer in order to promote a positive behaviour change was unsuccessful.